Socio-Demographic Determinants Influencing Institutional Delivery Utilization Among Women Aged 15-49 in Sudurpashchim Province, Nepal - Bohara, Pradeep Kumar; Khanal, Tantrika Raj; Devkota, Bijaya Mani (Nepal Population Journal, 2026)
Maternal mortality is a severe health issue of public concern in low- and middle-income countries (LMICs) in which a high percent of women still delivers babies without careful help. The inclusion of institutional delivery is well identified as an important intervention in the reduction of maternal and neonatal morbidity and mortality. This study has discussed socio demographic factors predicting institutional delivery among women age 15-49 years based on the Nepal Demographic and Health Survey 2022 (NDHS). The sample size of the analysis was 262 women who gave a live birth within five years before the survey was conducted. Patterns of service utilization were described using descriptive statistics, whereas binary logistic regression that considers the complex survey design was used to discover significant predictors. Younger women, more educated women, females who lived in urban areas, and those in richer families tended to deliver in an institution more often. But birth order and maternal education were the only variables that were statistically significant in the multivariate analysis. The birth order had an inverse relationship with institutional delivery but positive correlation with maternal education. There was no significant relationship between residence and household wealth and institutional delivery, perhaps due to the impact of recent health-system interventions. These results imply that the policies need to be more oriented towards female education and community awareness campaigns that support facility-based births, with a special focus on women with higher-order births and those belonging to marginalized groups.